Social Work Education and Homelessness: Mobilising Academia-Industry Partnerships to Create a Homelessness Subject - Watson, Juliet; Nipperess, Sharlene; Johnson, Guy (Australian social work, 2023)
Homelessness is a significant issue facing many Australian people, and one that social workers are likely to encounter in their professional lives. At present, though, there are no guidelines for social work programs on how to transfer homelessness knowledge into social work education programs. Social work curricula need to be informed by homelessness research, policy, and practice to reflect the contemporary Australian terrain, and to be responsive to emerging concerns. One approach, discussed in this article, is the mobilisation of an academia-industry partnership to create a dedicated homelessness subject for social work students. The subject, profiled here, offers an example of how social work can incorporate homelessness knowledge to benefit graduates, the sector, consumers, and academia. IMPLICATIONS Homelessness is a critical issue for social work practice, policy, and research, the impacts of which graduates are likely to encounter regardless of their specific fields of practice. There are no current guidelines for including homelessness in Australian social work education programs. A dedicated social work subject can furnish graduates with a strong foundation for entering the homelessness sector. Academia-industry partnerships have the potential to provide a systematic method of translating homelessness knowledge to future social workers through educational programs.